THE EFFECT OF SELF CONFIDENCE, QUALITY EDUCATION AND FAMILY ENVIRONMENT ON INDONESIAN YOUTH IN ENTREPRENEURSHIP - Novita, Novita; Irawan, Damar Aji; Suwitorahardjo, Benyamin (Bina Nusantara University, 2017)
The biggest challenge faced by students nowadays and in the future, is how to deal with the increasingly high competition in the world, the increasing number of undergraduate and limited job opportunities. In this kind of situations, the students had to find a creative way and change the approach of being a university graduate looking for a job, to become scholars who can create their own jobs, or even able to create jobs for others.The purpose of this study was to determine the youth interest on entrepreneurship in Indonesia. It seems that the youth are unaware to see that the job is increasingly difficult to find nowadays. So through this study, researchers wanted to find out what causes youth in Indonesia, reluctant to become an entrepreneur. While being an entrepreneur, the youth can open or create jobs for others and can reduce the level of unemployment in Indonesia.Self-confidence is an important factor in entrepreneurship. Family environment and quality education also participate in creating interest for youth in entrepreneurship. This research is using basic research method; where researchers will try to link the theories of the existing variables. Thus, researchers can conduct research by distributing questionnaires to the youth throughout Indonesia. This study aims to determine the cause of Indonesian youth lack of interest in entrepreneurship.